Rudorffites and Beyond: Perovskite‐Inspired Silver/Copper Pnictohalides for Next‐Generation Environmentally Friendly Photovoltaics and Optoelectronics. (19th July 2022) - Chakraborty, Abhisek; Pai, Narendra; Zhao, Jing; Tuttle, Blair R.; Simonov, Alexandr N.; Pecunia, Vincenzo
Abstract: In the wake of lead‐halide perovskite research, bismuth‐ and antimony‐based perovskite‐inspired semiconducting materials are attracting increasing attention as safer and potentially more robust alternatives to lead‐based archetypes. Of particular interest are the group IB–group VA halide compositions with a generic formula A x B y X x +3 y (A +  = Cu + /Ag + ; B 3+  = Bi 3+ /Sb 3+ ; X –  = I – /Br – ), i.e., silver/copper pnictohalides and derivatives thereof. This family of materials forms 3D structures with much higher solar cell efficiencies and greater potential for indoor photovoltaics than the lower‐dimensional bismuth/antimony‐based perovskite‐inspired semiconductors. Furthermore, silver/copper pnictohalides are being investigated for applications beyond photovoltaics, e.g., for photodetection, ionization radiation detection, memristors, and chemical sensors. Such versatility parallels the wide range of possible compositions and synthetic routes, which enable various structural, morphological, and optoelectronic properties. This manuscript surveys the growing research on silver/copper pnictohalides, highlighting their composition–structure–property relationships and the status and prospects of the photovoltaic and optoelectronic devices based thereon. The authors hope that the insights provided herein might accelerate the development of eco‐friendly and stable perovskite‐inspired materials for next‐generation photovoltaics and optoelectronics. Abstract : Silver/copper pnictohalides (A x B y X x +3 y, A +  = Cu + /Ag + ; B 3+  = Bi 3+ /Sb 3+ ; X –  = I – /Br – ) and their derivatives are eco‐friendly perovskite‐inspired materials with attractive optoelectronic properties and considerable capabilities for photovoltaics, photodetection, and beyond. This review surveys for the first time this growing research area, providing a cross‐sectional view of the composition‐structure‐property relationships of these materials and their potential for next‐generation photovoltaics and optoelectronics.